Decision Support System for Teacher Decision Following Teacher Professional Education (PPG) SMA / SMK East Kalimantan Province with Web-Based Smart Method - Dana Aulia Rahman; Heny Pratiwi; Hanifah Ekawati (Politeknik Pertanian Negeri Samarinda, 2021)
Teacher Professional Education (PPG) for SMA / SMK in East Kalimantan Province is higher education after an undergraduate education program that prepares students to have jobs with special skills requirements to become teachers. The problems in registration that occur at the East Kalimantan Provincial Education and Culture Office are: The calculation of the test data is still calculated manually, so it is necessary to build a Decision Support System for Determination of Participants in the Professional Teacher Education (PPG) for SMA / SMK in East Kalimantan Province using the Web-based SMART Method. The data collection method uses the observation method and the system development method uses the method of the decision support system, namely the intelligence, design, choice, and implementation stages. Because this method has clear, practical stages. Then the system testing is White Box and Beta Testing. With the existence of a Decision Support System for Determining Who Participates in Professional Education for Teachers (PPG) for SMA / SMK in East Kalimantan Province with the Web-based SMART Method, it can handle the calculation process when the test has been implemented. In the test results it can be concluded that the results of testing the questionnaire questions to ten (10) respondents can be concluded that more than 78.2% of respondents answered that the Determination Decision Support System Participating in Teacher Professional Education (PPG) at the High School / Vocational School Level of East Kalimantan Province with the SMART Method Web-based meets the criteria for a good website or web application. With the existence of a Decision Support System for Determining Who Participates in Professional Education for Teachers (PPG) for SMA / SMK in East Kalimantan Province with the Web-based SMART Method, it can handle the calculation process when the test has been implemented. In the testing results it can be concluded that the results of testing the questionnaire questions to ten (10) respondents can be concluded that more than 78.2% of respondents answered that the Determination Decision Support System Participating in Teacher Professional Education (PPG) for SMA / SMK in East Kalimantan Province with the SMART Method Web-based meets the criteria for a good website or web application. With the existence of a Decision Support System for Determining Who Participates in Professional Teacher Education (PPG) at the SMA / SMK in East Kalimantan Province with the Web-based SMART Method, it can handle the calculation process when the test has been implemented. In the testing results it can be concluded that the results of testing the questionnaire questions to ten (10) respondents can be concluded that more than 78.2% of respondents answered that the Determination Decision Support System Participating in Teacher Professional Education (PPG) for SMA / SMK in East Kalimantan Province with the SMART Method Web-based meets the criteria for a good website or web application. can handle the calculation process once the test has been executed. In the testing results it can be concluded that the results of testing the questionnaire questions to ten (10) respondents can be concluded that more than 78.2% of respondents answered that the Determination Decision Support System Participating in Teacher Professional Education (PPG) for SMA / SMK in East Kalimantan Province with the SMART Method Web-based meets the criteria for a good website or web application. can handle the calculation process once the test has been executed. In the testing results it can be concluded that the results of testing the questionnaire questions to ten (10) respondents can be concluded that more than 78.2% of respondents answered that the Determination Decision Support System Participating in Teacher Professional Education (PPG) for SMA / SMK in East Kalimantan Province with the SMART Method Web-based meets the criteria for a good website or web application.